Clinico-Pathological Investigation of Chicken Coccidiosis at Different Upazila in Bogura District - Islam, Md Mofizul; Ali, Md Haydar; Islam, Md Nazrul; Akther, Mahfuza; Rahman, Md Gausur (Research in Agriculture Livestock and Fisheries, 2020)
The experiment was conducted with the interest to know the overall condition of coccidiosis in small scale commercial poultry farms at different upazilla in Bogura district and the investigation was done from July to December, 2018. A thorough clinical and necropsy examination was done for characterizing the clinical signs, recording of gross lesions and collection of different organs mainly the small intestine and the caecum for further histopathological examination. A total of 343 suspected and dead chickens were examined, among them 52 (15.38%) (20.6% in broiler, 10.47% in sonali, 10.25% in layer) chickens were found positive for chicken coccidiosis. The proportional mortality rates were 19.25%, 21.42%, 8.23% and 7.5% respectively in age group of 0-4 weeks, 5-6 weeks, 7-8 weeks and above 8 weeks and the highest value was found in age group of 5- 6 weeks. Depression, ruffled feather, bloody diarrhoea, anaemia, drooping of wings and reduction of feed and water intake were commonly observed. Several gross changes were recorded including enlargement and discoloration of caecum, pinkish or blood mixed catarrhal contents in the intestinal lumen with numerous haemorrhagic lesions over intestinal mucosa. Histopathologically there was architectural destruction of caecum, destroyed and disorganized villi mucosa without any continuation of the lining epithelium. Some facts like farmers knowledge, the bio-safety measures and different protection programs with vaccination against the disease did not properly comply with the approved standards. Thus consideration of such points in management program of coccidiosis can improve the poultry farms of Bogura district. Res. Agric., Livest. Fish.7(2): 267-274, August 2020